The genome of Caenorhabditis bovis - Stevens, L.; Rooke, S.; Falzon, Laura C.; Machuka, Eunice M.; Momanyi, Kelvin N.; Murungi, Maurice K.; Njoroge, Samuel M.; Odinga, Christian O.; Ogendo, A.; Ogola, J.; Fèvre, Eric M.; Blaxter, M. (Elsevier, 2020)
The free-living nematode Caenorhabditis elegans is a key laboratory model for metazoan biology. C. elegans has also become a model for parasitic nematodes despite being only distantly related to most parasitic species. All of the ∼65 Caenorhabditis species currently in culture are free-living, with most having been isolated from decaying plant or fungal matter. Caenorhabditis bovis is a particularly unusual species that has been isolated several times from the inflamed ears of Zebu cattle in Eastern Africa, where it is associated with the disease bovine parasitic otitis. C. bovis is therefore of particular interest to researchers interested in the evolution of nematode parasitism. However, as C. bovis is not in laboratory culture, it remains little studied. Here, by sampling livestock markets and slaughterhouses in Western Kenya, we successfully reisolated C. bovis from the ear of adult female Zebu. We sequenced the genome of C. bovis using the Oxford Nanopore MinION platform in a nearby field laboratory and used the data to generate a chromosome-scale draft genome sequence. We exploited this draft genome sequence to reconstruct the phylogenetic relationships of C. bovis to other Caenorhabditis species and reveal the changes in genome size and content that have occurred during its evolution. We also identified expansions in several gene families that have been implicated in parasitism in other nematode species. The high-quality draft genome and our analyses thereof represent a significant advancement in our understanding of this unusual Caenorhabditis species.